One Year Survival of Wild-Type Adenocarcinoma Lung Cancer Patients Receiving Chemotherapy at dr. Saiful Anwar Hospital, Malang - Ungky Agus Setyawan; Hendy Setyo Yudhanto; Aura Madarina (Indonesian Society of Respirology (ISR), 2022)
Background: Lung cancer is one of the most common malignancies that leads to mortality. In Indonesia, lung cancer ranks first in men and third in women. The most common histological type of lung cancer is adenocarcinoma. Adenocarcinoma lung cancer is divided into 2 types, namely EGFR mutations and no mutations (wild-type). Chemotherapy is the treatment of choice for advanced wild-type adenocarcinoma lung cancer. This study aimed to assess the one-year survival of wild-type adenocarcinoma lung cancer patients receiving chemotherapy. Method: This study used a cross-sectional study design.Data were taken from the medical records of cancer patients at Dr. Saiful Anwar Hospital Malang in 2018-2019. Data were processed and analyzed by chi-square test. Results: Of the 54 subjects, 24 patients received carboplatin/ pemetrexed (44.4%), 15 patients received carboplatin/paclitaxel (27.8%), 9 patients received carboplatin/gemcitabine (16.7%), 2 patients received pemetrexed (3.7%), and 4 patients received gemcitabine (7.4%). The chemotherapy drug regimen had no correlation with one-year survival (P=0.899). Conclusion: There wasno significant difference between one-year survival andchemotherapy drug regimens. This study required a larger sample to minimize bias.